A de novo loss‐of‐function DYNC1H1 mutation in a patient with parkinsonian features and a favourable response to levodopa. Issue 5 (15th December 2017) - Szczałuba, K.; Szymańska, K.; Rydzanicz, M.; Ciara, E.; Walczak, A.; Piekutowska‐Abramczuk, D.; Kosińska, J.; Jacoszek, A.; Czerska, K.; Biernacka, A.; Laure‐Kamionowska, M.; Gasperowicz, P.; et al.
Abstract : Graphical summary of 'A de novo loss‐of‐function DYNC1H1 mutation in a patient with parkinsonian features and a favourable response to levodopa' by Szczałuba et al..